2010
DOI: 10.14741/ijcet/spl.2.2014.03
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of Process Parameters for TIG Welding based on Taguchi Method

Abstract: The present study pertains to the improvement of ultimate load of stainless steel -mild steel weld specimen made of tungsten inert gas (TIG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…The welding current with an F-value of 122 has the most significant effect on the tensile strength while the welding speed and GFR with F-values of 56 and 17 respectively have sub-significant effect. This result is in agreement with the work of Choudhury et al (2014) which revealed that current and GFR contributed significantly to the UTS of the TIG welded joints.…”
Section: Tensile Strengthsupporting
confidence: 93%
See 1 more Smart Citation
“…The welding current with an F-value of 122 has the most significant effect on the tensile strength while the welding speed and GFR with F-values of 56 and 17 respectively have sub-significant effect. This result is in agreement with the work of Choudhury et al (2014) which revealed that current and GFR contributed significantly to the UTS of the TIG welded joints.…”
Section: Tensile Strengthsupporting
confidence: 93%
“…It was found that GFR plays a significant on the chemical composition and properties of the weld joints. Choudhury et al (2014) worked on the design optimization of process parameters for GTAW of dissimilar metals of SS and mild steel based on Taguchi and ANOVA method. The main effects plots revealed that current and GFR contributed significantly to the ultimate tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated values of Analysis of Variance for Ultimate Tensile Strength of welding joint are listed in table 5. The calculated values of ANOVA present the percentage effect of each parameter on Ultimate Tensile Strength of the joint.…”
Section: ) Analysis Of Variance (Anova) Results For Utsmentioning
confidence: 99%
“…From this study they concluded that the welding current and welding speed are the major factors affecting tensile strength of welded joints. [5] Ajit hooda, Ashwani dhingra & Satpal sharma has done their research on optimization of MIG welding parameters in order to improve yield strength of AISI 1040 mild steel. The process parameters welding current, voltage, gas flow rate and wire speed were studied.…”
Section: IImentioning
confidence: 99%
“…Some research has been done on the selection of the welding process, but none of them deal with choosing the welding process using hard-facing to repair the shredder hammer. Choudhury, Bandyopadhyay, and Rudrapati (2014) studied about welding process selection used confidence level for each qualifier. Ravisankar, Balasubramanian, and Muralidharan (2006) used analytic hierarchic process (AHP) as a method for welding process selection of high strength aluminum alloys to fabricate butt joint.…”
Section: Introductionmentioning
confidence: 99%